FORENSIC EXPERT CHARACTERISTICS OF THE HUMAN GENOMEAND ITS IDENTIFICATION SIGNS - Кофанов, Андрій Віталійович; Ергард, Наталія Миколаївна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2021)
Purpose: introduction into expert practice of new methods of research of human biological traces to increase the level of identification capabilities. Research methods: comparative legal analysis, cognitive-analytical, etc. Results: it’s suggested that an innovative understanding of such basic legal properties of evidence as their significance, good quality and reliability and solution to the issue of criminal and other legal liability for violation of the procedure for obtaining evidence. Discussion: it’s emphasized that significant progress in obtaining identification evidence of a person’s involvement in a crime based on traces of biological origin has been achieved primarily through the use of molecular genetics. Molecular genetic analysis of DNA is only one of the stages of identification, and to obtain the final result requires statistical analysis of the data, especially important when the genotypes of the offender and the suspect: in this case it is sometimes about human life. Objects of biological origin that are removed as evidence from the scene include blood, semen, saliva, sweat, hair, vaginal secretions, urine, excrements, organs and tissues of the human body, bones and their fragments. The source of traces of biological origin is the human body, its organs. Under specific conditions, they, and especially blood, carry information about the mechanisms and circumstances of the crime. The shape of the traces of blood reflects the nature of the wounds, indicates some actions of the subject of the crime, the type of weapon used, and so on. Surveying the scene when looking for traces of biological origin, such as traces resembling blood, should be targeted, depending on the type of crime. The study of the shape of blood traces allows to model the mechanism of the crime. Such research is carried out at inspection of a scene. It allows you to establish the location and posture of the victim and the offender at the time of injury, the trajectory of the wounded, the special characteristics of the offender, the type of instrument of the crime and more. Trace detection should be done very carefully so as not to damage not only the tracks but also the media. Participants in the inspection should move only beyond the territory already inspected by the investigator. It is important to ensure that the inspection procedure is such that participants do not leave their own marks on the scene and in the areas not inspected. Thus, the search for and collection of traces of biological origin of man is based on the general principles of search activity. To date, the method of DNA analysis (genotyping) is one of the most promising areas of forensic expertise and its results are a fairly reliable proof of involvement in the crime of a particular person.